Al descubrimiento de sí mismas - González Sarmiento, Olga (2013)
The article is about the lives of women who have survived adverse situations or have participatedwith distinction in the task of helping other women to do so.Part of the idea that women possess much inner strength that allows us to build ourselves, rebuildand even help others to do so, when necessary.In short, it focuses on the positive message that give us the life of six exceptional women who,perhaps embody many others with similar backgrounds and development, but by their actionsremind us that, even though we live situations difficult to overcome; will, faith, fortitude, loveothers, love ourselves can help us not only overcome them, but to assist in the development andgrowth of others who are in similar situations.